Second main theorem for Holomorphic curves intersecting a Fermat-type hypersurface in projective spacel - Nguyen, Thi Xuan Mai; Pham, Truc Lam; Nguyen, Dang Khai; Tran, Nhat Minh (Hue University Journal of Science: Natural Science, 2025)
Let $s, b, d$ be positive integers with $(s+bd)-(n+1)(s+bn)>0$. Let $R_{i}$ be homogeneous polynomials of degree $s$ and $Q_i$ be homogeneous polynomials of degree $b$. For an algebraically non-degenerate holomorphic curve $f\colon\mathbb{C}→\mathbb{C} \mathbb{P}^n$, for a Fermat-type hypersurface of the form $\sum_{i=0}^{n} Q_i R_{i}^{d}=0$, we obtain a Second Main Theorem type estimate in which the counting function are truncated to level $n$.